2016
DOI: 10.1055/s-0036-1588060
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and Topographical Classification of Craniopharyngiomas: A Literature Review

Abstract: Craniopharyngiomas (CPs) are clinically relevant tumors of the sellar region and are associated with high morbidity and occasional mortality. There are two different subtypes of CPs that differ clinically and pathologically: adamantinomatous CP and papillary CP. The differential diagnosis is still challenging even with developments in preoperative imaging as several tumors of the sellar/parasellar region share a continuum of clinical characteristics and imaging similarities. Several topographical classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 62 publications
1
48
0
Order By: Relevance
“…Craniopharyngiomas (CPs) are tumours that may develop from the sella to the third ventricle and constitute approximately 3% of all intracranial tumours [8]. They are the most common form of non-neuroepithelial neoplasm in paediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Craniopharyngiomas (CPs) are tumours that may develop from the sella to the third ventricle and constitute approximately 3% of all intracranial tumours [8]. They are the most common form of non-neuroepithelial neoplasm in paediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…There are two histological subtypes of craniopharyngioma: the adamantinous and papillary types [ 1 ]. The adamantinomatous variant is much more common than papillary variant (9 : 1) and are pathologically distinct [ 3 ]. Squamous-papillary craniopharyngiomas are predominantly solid or mixed solid-cystic masses, which are often observed in adults at suprasellar location.…”
Section: Discussionmentioning
confidence: 99%
“…Craniopharyngiomas are rare benign epithelial tumors, arising from the pituitary stalk or gland and developing in the sellar and parasellar region of the central nervous system and constitute approximately 3% of all intracranial tumors [ 1 , 2 ]. These rare tumors are the most common form of nonneuroepithelial neoplasms in pediatrics [ 3 ]. Several cases of craniopharyngioma arising from unusual locations other than the sellar and parasellar regions have been described in the literature [ 3 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological behavior of CPs varies from patient to patient in that while some remain stable even up to 30 years before symptomatic recurrence [29], others may grow rapidly within an erratic period of time [2] It has been reported that most recurrences appear during the first 5 years following treatment [6] [30]. Similar to primary CPs, the clinical symptoms of RCPs are inconstant, on account of the variable topographical location [31]. CPs of suprasellar region commonly present with headache, visual field defects, and endocrine dysfunctions [32].…”
Section: Cp Recurrence and Clinical Manifestationmentioning
confidence: 99%